A processing method of generating S(α, β, T) tables considering resonance elastic scattering kernel for the Monte Carlo codes - Zu, Tiejun; Xu, Jialong; Cao, Liangzhi (Progress in nuclear energy (New series), 2020)
It has been proved that resonance elastic scattering kernel (RESK) has significant impact on the energy and angle distributions of the secondary neutrons, and consequently affects the eigenvalues and fuel temperature coefficients. Therefore, it is necessary for the nuclear data processing codes to generate the accurate data considering RESK for the neutronics analysis. In this paper, a processing method is proposed to generate the S(α, β, T) tables efficiently for Monte Carlo codes to account for the RESK. A multi-point linearization method is developed to generate the incident energy grids of S(α, β, T) tables, which can minimize the data size of S(α, β, T) tables without losing accuracy. The equally probable cosines in S(α, β, T) tables are obtained by solving the sets of nonlinear equations which are established by Legendre polynomials and the differential moments of RESK. The generation procedure of the S(α, β, T) tables is more practical by using the proposed calculation method of equally probable cosines. Based on the proposed processing method, a new module is developed in the nuclear data processing code called NECP-Atlas. The ACE-format libraries with the S(α, β, T) tables are generated by NECP-Atlas and supplied to the OpenMC code to perform the verifications. The numerical results show that the impact on eigenvalues caused by the RESK can be reflected correctly by the Monte Carlo calculations using the S(α, β, T) tables. Meanwhile, the results based on the S(α, β, T) tables match well with those based on the Doppler broadening rejection correction approach. •A method for generating S(α, β, T) tables considering resonance elastic scattering kernel is proposed.•The processing method is a highly efficient method and the accuracy of S(α, β, T) tables is high.•The ACE-format libraries are generated by NECP-Atlas and several benchmarks are calculated.